Influence of oocyte retrieval methods and maturation media on in vitro development of porcine embryos - Maqhashu, Ayanda (University of Pretoria, 2021)
Dissertation (MSc Agric Animal Science (Reproduction Physiology))--University of Pretoria,2020.